Trans‐right atrial access to the left ventricle for catheter ablation of ventricular tachycardia in patients with mechanical aortic and mitral valves. Issue 2 (20th September 2022) - Gökdeniz, Teyyar; Karavelioglu, Yusuf; Akgün, Taylan; Çelik, Muhammet Cihat
Abstract: The presence of mechanical heart valves in both aortic and mitral positions is a significant limitation for traditional left ventricular (LV) access, including retrograde transaortic and/or antegrade interatrial transseptal routes. We present a case of successful catheter ablation for ventricular tachycardia via a traditional transfemoral venous approach, which involves direct puncture of the inferior and medial aspect of the right atrium adjacent to the posteroseptal process of LV (PSPLV). Percutaneous trans‐right atrial access to the left ventricle appears to be a safe and feasible method for catheter ablation of ventricular tachycardia in patients with mechanical aortic and mitral valves.